Seasonal Dynamics of Epigeic Arthropods under the Conditions of Ecological Management of the Triticum aestivum Crop - Vladimír Langraf; Kornélia Petrovičová (Agriculture, 2024)
The policy of the European Union on land management promotes sustainable agriculture with an emphasis on the protection of biodiversity and the environment. Organic agriculture is the most appropriate alternative to ensure this common goal. The aim of this study was to determine the influence of factors such as pH, moisture, nitrogen potassium, phosphorus and grass herbaceous vegetation on the spatial structure of epigeic arthropods during the spring and summer seasons under organic farming conditions. Research took place between 2020 and 2022, and we recorded 14,988 individuals belonging to 16 taxa using pitfall traps. Between the years 2020 and 2022, we confirmed a decrease in the number of individuals and taxa of epigeic arthropods from the grass herbaceous vegetation to the interior of the field during the summer seasons. This decline was not confirmed in the spring seasons. Phosphorus, potassium, nitrogen, moisture and pH factors also had a significant influence on the spatial structure of epigeic arthropods. Our results show that the higher number of individuals and taxa at the grass herbaceous vegetation occurred only during the summer period. This fact contributes to an increase in biomass and, consequently, the yield of crops.